Desempleo desbordado - Sarmiento, Eduardo (Diario El Espectador, 2011)
La economía no va bien. En febrero el desempleo aumento con respecto al año pasado y se sitúo en el nivel más alto de América Latina. El empleo creció menos que la población y se ubica por completo en la informalidad.

The economy is not doing well. In February unemployment increased compared to the year past and was placed at the highest level in Latin America. Employment grew less than the population and is completely informal.
Keywords: Desempleo - Colombia; Economía - Colombia; Desarrollo económico - Colombia; Unemployment - Colombia; Economy - Colombia; Economic development - Colombia